2010
DOI: 10.1140/epjb/e2010-00219-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of assortativity and degree-preserving rewiring on the spectra of networks

Abstract: Abstract. Newman's measure for (dis)assortativity, the linear degree correlation coefficient ρD, is reformulated in terms of the total number N k of walks in the graph with k hops. This reformulation allows us to derive a new formula from which a degree-preserving rewiring algorithm is deduced, that, in each rewiring step, either increases or decreases ρD conform our desired objective. Spectral metrics (eigenvalues of graph-related matrices), especially, the largest eigenvalue λ1 of the adjacency matrix and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 22 publications
6
125
0
Order By: Relevance
“…1(a)-(e)). The largest eigenvalue exhibits an increasing trend as already discussed in [28,29]. As network is rewired entailing disassortativity, spectral distribution (ρ(λ)) acquires a very different structure than those of the assortative networks.…”
Section: Resultsmentioning
confidence: 61%
“…1(a)-(e)). The largest eigenvalue exhibits an increasing trend as already discussed in [28,29]. As network is rewired entailing disassortativity, spectral distribution (ρ(λ)) acquires a very different structure than those of the assortative networks.…”
Section: Resultsmentioning
confidence: 61%
“…Motivated by this observation, Winterbach et al (2012) introduced an algorithm to compute a network with maximal or minimal assortativity given a vector of valid node degrees using degree-preserving rewiring (Maslov & Sneppen, 2002) and weighted b-matching (Muller-Hannemann & Schwartz, 1999). Degree-preserving link rewiring is effective in decreasing or increasing the assortativity of a network graph without affecting the degree distribution of the vertices (Van Mieghem et al, 2010). Holme & Zhao (2007) also found that an increase in the assortativity of a graph (accomplished through degree-preserving rewiring) also contributes to an increase in the maximum modularity, average hop count, effective graph resistance as well as a decrease in the number of clusters.…”
Section: Related Workmentioning
confidence: 99%
“…Some weaknesses in modularity optimization have also been determined, such as the incapability to detect communities smaller than a resolution limit [5] or the breaking up of large random sub-graphs into separate communities [6]. A spectral analysis of the modularity as well as correlation with other metrics, such as assortativity [23,24], has been conducted in [25].…”
Section: Related Workmentioning
confidence: 99%